Economic uncertainty and bank stability: Conventional vs. Islamic banking - Bilgin, Mehmet Huseyin; Danisman, Gamze Ozturk; Demir, Ender; Tarazi, Amine (Journal of Financial Stability, 2021)
In this paper, we explore whether economic uncertainty differently affects the default risk of Islamic and conventional banks. Using a sample of 568 banks from 20 countries between 2009 and 2018, we use the World Uncertainty Index (WUI) by Ahir et al. (2018) to conduct a study based on a comparable measure across countries. Our findings indicate that economic uncertainty increases the default risk of conventional banks but does not affect Islamic banks’ default risk. To understand why, we explore the influence of religiosity, institutional factors, and bank-level heterogeneity. We observe that Islamic banks’ default risk is not significantly affected by uncertainty in all types of countries, but such a difference with conventional banks mainly holds for banks with higher income diversification, larger size, and that are publicly traded. Moreover, our findings show that conventional banks suffer more from uncertainty in terms of stability in countries with higher religiosity and with a higher share of profit-loss sharing (PLS) contracts. Our results are robust to alternative estimation techniques to deal with endogeneity and to alternative variable measurements.